Planting a city in the tropical Andes - Molina Franco, Diego Alejandro, author. Link
1 online resource (xiii, 206 pages)
Keywords: "This book reveals how the 19th Century modernisation of Bogotá led to a transformation in the social role of plants - showing how this city located in the high altitudes of the tropical Andes turned into a 'floristic island' formed by native, introduce, wild and cultivated plants. Urbanisation is one of the main forces behind biodiversity loss. Paradoxically, the expansion of cities has made urban environment spaces with a greater numbers of plant species compared to their surrounding areas. Planting a City in the Tropical Andes takes a multidisciplinary approach to shed light on the cultural and ecological mechanisms that have transformed modern cities into what can be described as 'floristic islands'. By drawing upon a wide array of historical sources, this book explains how the 19th-century modernization of Bogotá (Colombia), led to the replacement of traditional botanical practices with technical knowledge, which in turn endowed the city with a unique floristic inventory. Through a unique botanical perspective on Latin American urban history, this book uncovers how capitalist dynamics in Bogotá transformed plants into providers of clean air and water and their use in the urban landscape contributed to the cultivation of disciplined citizenry. Placing plants at the forefront of its narrative, the book offers an original contribution to the underexplored history of horticulture in tropical Latin America. It serves as a compelling example of how the creative and conflicting forces of the Anthropocene have forged new environments and previously unseen relationships between people and plants. This volume will be of great use to scholars and students interested in social history, urban environmental histories and cultural history"--